2019
DOI: 10.3390/app9132680
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Organic Matter and Tetracycline in Water by Using Constructed Wetlands and Photocatalysis

Abstract: In this study, the ability of a bench-scale simulated constructed wetland (CW) to remove organic matter (OM) and tetracycline (TC) from water was examined. The performance of CW was evaluated by varying the initial concentrations of the target compounds and the hydraulic retention times (HRTs). Findings showed that OM removal efficiencies were 55.2–80.8%, 28.1–71.9% and 72.1–79.7% for ultraviolet absorbance at 254 nm (UV-254), dissolved organic carbon (DOC) and soluble chemical oxygen demand (sCOD) respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The removal of EPs by CWs is mainly through the absorption and degradation (Li, Gao, et al, 2019; Li, Li, et al, 2019; Li, Zhang, Zeng, et al, 2019; Li, Liu, Zhang, Li, et al, 2019; Li, Zhang, Xia, Wang, et al, 2019; Li, Zhang, Hu, et al, 2019; Li, Sun, Zhang, Feng, et al, 2019; Li, Wang, et al, 2019; Li, Yuan, Gao, et al, 2019; Rabello et al, 2019). Adsorption is an important way to remove EPs, and the substrate, soil, and sediment of packed bed in CWs play major roles in adsorption (Nguyen, Chao, & Chen, 2019; Nguyen, Afzal, et al, 2019; Sardana, Cottrell, Soulsby, & Aziz, 2019; Zhao, Yan, et al, 2019; Zhao, Jian, et al, 2019). The degradation of EPs in CWs is mainly through microbial degradation, photolysis, and hydrolysis (Tara et al, 2019).…”
Section: Engineered Wetlands and Natural Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal of EPs by CWs is mainly through the absorption and degradation (Li, Gao, et al, 2019; Li, Li, et al, 2019; Li, Zhang, Zeng, et al, 2019; Li, Liu, Zhang, Li, et al, 2019; Li, Zhang, Xia, Wang, et al, 2019; Li, Zhang, Hu, et al, 2019; Li, Sun, Zhang, Feng, et al, 2019; Li, Wang, et al, 2019; Li, Yuan, Gao, et al, 2019; Rabello et al, 2019). Adsorption is an important way to remove EPs, and the substrate, soil, and sediment of packed bed in CWs play major roles in adsorption (Nguyen, Chao, & Chen, 2019; Nguyen, Afzal, et al, 2019; Sardana, Cottrell, Soulsby, & Aziz, 2019; Zhao, Yan, et al, 2019; Zhao, Jian, et al, 2019). The degradation of EPs in CWs is mainly through microbial degradation, photolysis, and hydrolysis (Tara et al, 2019).…”
Section: Engineered Wetlands and Natural Systemsmentioning
confidence: 99%
“…The degradation of EPs in CWs is mainly through microbial degradation, photolysis, and hydrolysis (Tara et al, 2019). In addition, EPs can be also absorbed by roots, stems, and leaves of plants in CWs (Nguyen, Chao, et al, 2019; Nguyen, Afzal, et al, 2019). The factors affecting the removal efficiency of CWs include treatment temperature, CW configuration, and plant species.…”
Section: Engineered Wetlands and Natural Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they also reported the first‐order removal rate coefficients for selected EOCs (Nivala, Kahl, et al, 2019). More than 80% of tetracycline was removed in a bench‐scale simulated CW in the first two hours of operation through the absorption process (Nguyen, Nguyen, et al, 2019).…”
Section: Wetlands For Emerging Pollutants Removalmentioning
confidence: 99%
“…Plenty of studies showed that the exotic plant invasion might affect the accumulation of soil organic carbon (SOC) and organic nitrogen (ON) [8,9]. Soil organic matter (SOM) is the main form of OC and ON, the study on different SOM categories can further reveal the influence of alien plant invasion on the accumulation process of carbon and nitrogen [10]. The SOM can be divided into light fraction organic matter (LFOM) and heavy fraction organic matter (LFOM), through soil density difference [11].…”
Section: Introductionmentioning
confidence: 99%